2006
DOI: 10.1021/la061553b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peptide Ligand Dipole Moments on the Redox Potentials of Au38 and Au140 Nanoparticles

Abstract: Phenylethanethiolate monolayer-protected Au38 and Au140 nanoclusters were modified by ligand place exchange with a series of thiolated peptides. The peptides were homooligomers based on the alpha-aminoisobutyiric acid unit. The effects of changing the peptide concentration and the peptide length in the capping monolayer were studied by differential pulse voltammetry. The results showed that the redox behavior of the nanoparticles can be affected very significantly by such modifications. For example, the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 25 publications
9
90
0
Order By: Relevance
“…14 −19 On transition metal oxide semiconductors, the adsorption of structurally simple molecules to form polar layers was found to shift the position of the semiconductor conduction band and influence the open circuit photovoltage and other parameters in dye-sensitized solar cells. [20][21][22][23][24][25][26]11,13 As part of our interest in molecules/semiconductor interfaces, we recently demonstrated that two Zn(II) tetraphenylporphyrins having the structure porphyrin-linkeranchor with a reversible built-in dipole in the linker shift a molecule's energy levels alignment on transition-metal oxide in a predictable manner. 27 The proof-of-concept experiment, which was carried out on a ZnO (11−20) single crystal surface by UV photoemission spectroscopy (UPS), is illustrated in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%
“…14 −19 On transition metal oxide semiconductors, the adsorption of structurally simple molecules to form polar layers was found to shift the position of the semiconductor conduction band and influence the open circuit photovoltage and other parameters in dye-sensitized solar cells. [20][21][22][23][24][25][26]11,13 As part of our interest in molecules/semiconductor interfaces, we recently demonstrated that two Zn(II) tetraphenylporphyrins having the structure porphyrin-linkeranchor with a reversible built-in dipole in the linker shift a molecule's energy levels alignment on transition-metal oxide in a predictable manner. 27 The proof-of-concept experiment, which was carried out on a ZnO (11−20) single crystal surface by UV photoemission spectroscopy (UPS), is illustrated in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%
“…12,13,4856 Previous work showed that its stability is also unaffected under conditions of ligand exchange with exogenous thiols, including thiolated peptides. 12,13,48,52 Monodisperse Au 144 (SCH 2 CH 2 Ph) 60 was prepared as described previously. 13,52 Briefly, AuCl 4 – was transferred from an aqueous solution to toluene using tetraoctylammonium bromide.…”
Section: Resultsmentioning
confidence: 99%
“…35 Although the curvature of the gold core minimizes the steric hindrance between neighboring ligands, 36 the footprint of helical peptides is significantly larger than that of simpler molecular chains such as phenylethanethiol and S-OctA; however, the use of the sufficiently long thiolated tether, −S−(CH 2 ) 4 CO−, in S-TCG is such to make the 1:1 exchange possible. To Au 144 TCG we can thus assign the average formula Au 144 (SC 2 H 4 Ph) 48 (S-TCG) 12 . The different loading attained with the two ligands is attributed to the time allowed for the exchange to occur, shorter than that probably required to attain equilibrium exchange, 11 and also to the different size, shape, and self-aggregation properties of the two ligands used.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The different loading attained with the two ligands is attributed to the time allowed for the exchange to occur, shorter than that probably required to attain equilibrium exchange, 11 and also to the different size, shape, and self-aggregation properties of the two ligands used. 12 Concerning the core of the exchanged MPCs, we checked the UV−vis pattern before and after exchange ( Figure S6 and S7). The spectra of Au 144 OctA and Au 144 TCG maintain the same features of the native cluster; in particular, only a barely detectable shoulder is visible at 520 nm, i.e., where the surface plasmon absorption of gold is expected to emerge as a band only for particles having diameters larger than ca.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation